Interactions Between Child-Rearing and Other Risk Factors in Predicting Delinquency, and Implications for Prevention - Farrington, David (International journal of offender therapy and comparative criminology, 2025)
This article aims to identify interactions between harsh discipline and poor supervision and other childhood risk factors (all measured at age 8–10) in predicting delinquency. It analyzes data collected in the Cambridge Study in Delinquent Development (CSDD), which is a prospective longitudinal study of 411 London males first assessed at age 8. Of these males, 26% were convicted between ages 10 and 17. Harsh discipline and poor supervision significantly predicted delinquency, as did 16 other childhood risk factors. Generally, harsh discipline predicted delinquency more strongly in the presence of other risk factors, whereas poor supervision predicted delinquency more strongly in the absence of other risk factors. It is suggested that parent training programs targeting harsh discipline should focus particularly on children and families who possess other risk factors, whereas parent training programs targeting poor supervision should focus particularly on children and families who do not possess other risk factors.